PENETAPAN HARGA HASIL PERIKANAN DALAM PERSPEKTIF EKONOMI ISLAM (STUDI KASUS DI TEMPAT PELELANGAN IKAN (TPI) MUNCAR KABUPATEN BANYUWANGI) - Aini, Aula Izatul; A, Komarudin; Rosita, Della Dwi (Jurnal Ekonomi Syariah Darussalam, 2022)
This study aims to find out how the practice of price fixing on fishery products in TPI Muncar, Banyuwangi Regency? as well as knowing how the practice of pricing on fishery products at TPI Muncar Banyuwangi Regency in the perspective of Islamic economics?. This study uses a qualitative method with descriptive analysis, which describes the data that the researchers collected both from observations, interviews and documentation during research at at TPI Muncar Banyuwangi Regency. The practice of fixing the prices set at TPI Muncar Banyuwangi Regency, there are two ways, the first is in the practice of fixing the prices carried out by the fish collectors Mrs. Kati and the fish collectors Mrs. Trima from methods such as the price competition method, and the pricing based on demand is appropriate with Islamic economics, while the pricing method used by Mr. Soep such as using the promotion method is still not in accordance with Islamic economics because it still contains elements of coercion.